Sobre o cogito como representação: a relação de si a si na filosofia primeira de Descartes - Borges, Marcos Alexandre (2009)
The cogito is the statement that expresses the first certainty of Cartesian philosophy. It is the relation of itself to itself, through which the ego becomes conscious of its existence. This research work develops the problem about the statute of cogito, analyzing the possibility of the I think therefore I am , or I am, I exist by Descartes, to be a representation. On the one hand, it seems that there is not a problem in considering the cogito a representation, since in the cogito, the ego has a thought, and all the representation is a thought; on the other hand, consider the cogito as representation is to consider that the thought of the ego about itself occurs in the same way as the thought of the ego about the other things. Therefore, it is necessary to investigate the notion of representation to analyze the possibility of the cogito to be thought in the representative patterns. The representation is a concept connected with the notion of idea, and to represent consists of having ideas, in realizing the presence of something through an idea. Things are represented to the ego because it does not have direct access to these things, which become present through the ideas that represent them. Having in view that in the cogito the object of thought is the own I-thinking, something that has direct access to itself, the cogito cannot be considered a representation. As things become present to the ego through the objective reality of ideas, and the representation is connected with the notion of objective reality reality that Descartes attributes an ontological inferior statute, since it does not express the own reality of one thing, but mere representation to represent means to realize the presence of the reality of something to what the ego does not have direct access. As the cogito expresses its own reality of the thing thought, and what is accessed is a formal reality, the cogito cannot be a representation, since a representation does not concern to the formal reality of something, but merely to the objective reality.